REVALUASI ASET UNTUK TUJUAN PERPAJAKAN, AMBIL ATAU JANGAN - YUSUF S. BASAR (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2016)
The Government has launched a policy of taxation through the Minister of Finance numbered 191/PMK.010/2015 on Revaluation of Fixed Assets Proposed in the Year 2015 and 2016. Impact of revaluation, automatically has consequences to the increase on depreciation expenses of fixed assets are charged to the profit and loss next period, so company will have benefit from the revaluation of these assets. But Fixed Assets Revaluation for tax purposes is not free. There are taxes to be paid, especially if the asset after revaluation is sold to a third party, then the taxpayer will be charged as additional income tax. If the company still wants to take the program of the asset revaluation, fixed assets after the revaluation prohibited for sale to another party until the depreciation of assets ending.